Behavioural repertoires in moving crowds: an observational approach - Anna Sieben; Tom Postmes (Royal Society Open Science, 2025)
The wide variety of behaviour found in crowds is a challenge for current models of crowd movement behaviour. To aid the development of a new generation of models, this paper develops a systematic observational approach based on social psychological knowledge about how humans recognize and use social meaning and structures. To develop this approach, we studied the movement behaviour of participants in a pedestrian crowd experiment, more specifically in four experimental runs (n = 351) of crowd situations, videotaped from a top-view perspective. In the experiments, large groups of around 80−90 imagined being on the way to a concert. There was no instruction for how to behave except that participants’ motivation to arrive at the gate first was varied through instructions (low/high). Through a qualitative, iterative process of systematic observation a complete list of behavioural repertoires (an ethogram) was collected. Behaviours were performed by either individuals, small interactive groups or large action groups. The observational dataset was enriched with pedestrian trajectory data, used to create heatmaps for density and speed, as well as time–distance plots. The analysis reveals that participants show many, sometimes rapid, changes both between movement repertoires and between the social unit they are engaged in.